Circulating microRNAs correlate with structural and functional MRI parameters in patients with multiple sclerosis - Geiger, Lili; Orsi, Gergely; Cseh, Tamás; Gombos, Katalin; Illés, Zsolt; Czéh, Boldizsár (Frontiers in Molecular Neuroscience, 2023)
Introduction: Circulating microRNAs are promising biomarkers for multiple sclerosis (MS). Our aim was to correlate serum microRNA levels with various magnetic resonance imaging (MRI) parameters. Methods: We recruited 50 MS patients and measured cervical spine and cerebral white matter lesions together with regional brain volumes. Microstructural changes in the white matter were investigated with diffusion tensor imaging. Magnetic resonance spectroscopy was performed to measure cerebral metabolites. Functional connectivity within the default mode network was examined with resting-state functional MRI. On the day of the MRI measurements, we collected serum samples and carried out quantitative analysis of ten pre-selected microRNAs using droplet digital PCR. Results: Serum level of miR-143.3p could differentiate between MS subtypes and had lower levels in progressive MS types. We found significant associations between microRNA levels and MRI measures: 1) higher miR-92a.3p and miR-486.5p levels were associated with greater total white matter lesion volumes within the cervical spine, 2) decreased miR-142.5p levels was associated with reduced total creatinine concentration and 3) miR-92a.3p, miR-142.5p and miR-486.5p levels were associated with functional connectivity strengths between specific nodes of the default mode network. Specifically, we found a negative association between miR-92a.3p and miR-486.5p levels and connectivity strength between the lateral temporal cortex and posterior inferior parietal lobule, and a positive association between miR-142.5p level and connectivity strength between the retrosplenial cortex and temporal pole. However, miRNA levels were not associated with regional brain volumes. Conclusion: We provide here further evidence that circulating microRNAs may show correlation with both structural and functional